2021
DOI: 10.12697/fce.2021.58.20
|View full text |Cite
|
Sign up to set email alerts
|

New assessment of Least Concern lichens in the Red List of Estonia: are common species still common?

Abstract: The threat status of 161 lichenized species that were considered common in Estonia was assessed in 2021. For most of these species, it was the second Red List assessment using the IUCN system (the first such evaluation was performed in 2008). The main data sources for species occurrence were the records reported in 100 study sites located throughout the country during 2020, and the PlutoF biodiversity database. 125 species remained, according to the new assessment, in the category Least Concern (LC) and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In principle, the same concept and the evaluation process as during the previous red list assessments of lichens in Estonia were used (Randlane et al, 2008;. The latest IUCN guidelines for using the Red List categories and criteria ( IUCN Standards andPetitions Subcommittee, 2017, 2019) were applied as well as supplementary guidelines for applying IUCN Red List criteria for fungi (Dahlberg & Mueller, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In principle, the same concept and the evaluation process as during the previous red list assessments of lichens in Estonia were used (Randlane et al, 2008;. The latest IUCN guidelines for using the Red List categories and criteria ( IUCN Standards andPetitions Subcommittee, 2017, 2019) were applied as well as supplementary guidelines for applying IUCN Red List criteria for fungi (Dahlberg & Mueller, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Of them, CR, EN and VU are threatened categories according to the IUCN guidelines. Similarly to the previous assessments (Randlane et al, 2008;, the species that had not been reliably reported from Estonia after 1950 were considered to be RE.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations